2015
DOI: 10.1038/srep15264
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Pattern and Socio-Economic Factors of Bacillary Dysentery at County Level in Sichuan Province, China

Abstract: Bacillary dysentery (BD) remains a big public health problem in China. Effective spatio-temporal monitoring of BD incidence is important for successful implementation of control and prevention measures. This study aimed to examine the spatio-temporal pattern of BD and analyze socio-economic factors that may affect BD incidence in Sichuan province, China. Firstly, we used space-time scan statistic to detect the high risk spatio-temporal clusters in each year. Then, bivariate spatial correlation and Bayesian spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 28 publications
(35 reference statements)
7
37
0
Order By: Relevance
“…A negative correlation of GDP per capita and child dysentery was observed, which means that the lack of economic production is associated with the health of children at the country level. This finding is consistent with other epidemiological studies, which present how the lack of economic resources at the country level is associated with the decrease and absence of opportunities and in turn with impaired health of the population [27,28].…”
Section: Discussionsupporting
confidence: 92%
“…A negative correlation of GDP per capita and child dysentery was observed, which means that the lack of economic production is associated with the health of children at the country level. This finding is consistent with other epidemiological studies, which present how the lack of economic resources at the country level is associated with the decrease and absence of opportunities and in turn with impaired health of the population [27,28].…”
Section: Discussionsupporting
confidence: 92%
“…This study found that 68,855 BD cases were reported in Chongqing from 2009 to 2016, with an average annual incidence of 29.394/100,000. Although BD incidence in Chongqing showed a downward trend overall, it was still higher than the incidence in the same period in China (20.28/100,000 in 2009, 15.29/100,000 in 2012, 11.24/ 100,000 in 2014) [21,22], the USA in 2016 (6.53/100, 000), Zhejiang Province between 2004 and 2015 (4.25/ 100,000) and Sichuan Province between 2004 and 2014 (22.12/100,000) [1,5,23], which highlights the serious situation regarding the prevention and control of BD in Chongqing. Chongqing has a subtropical monsoon humid climate and covers an area of 824,000 km 2 , of which 78% is mountainous; it has sufficient precipitation, a warm temperature and a suitable climate for the growth and reproduction of Shigella, which may be one of the reasons BD incidence in Chongqing is higher than that in other areas.…”
Section: Discussionmentioning
confidence: 94%
“…BD incidence was higher in men than in women in Chongqing, and the proportion of farmers was relatively large; this finding is consistent with other research results and may be attributed to that men are more likely to lack good health habits and to participate in group activities such as attending parties and dining out. Additionally, while the physical activity level of farmers is high, their working environments are frequently unsanitary [1,5,8,21,27]. This, coupled with a lack of knowledge of disease prevention and control, results in elevated incidences of BD among men and farmers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two indicators reflect the regional industrial structure and are widely used in studies [50,51]. Generally, the proportion of the tertiary industry is positively correlated with regional economic development.…”
Section: The Proportion Of Tertiary Industry In Gdp (Pti) and Secondamentioning
confidence: 99%